Peran komite audit pada sustainability disclosure - Yunike Lendengtariang; Irenius Dwinanto Bimo (Universitas Hayam Wuruk Perbanas, 2022)
The purpose of the study was to analyze the effect of size, independence, frequency of meetings, and financial expertise of audit committee members on sustainability disclosure. The sample was taken using a purposive sampling method, and the sample was public goods and consumption sector companies from 2015 to 2019. The number of sample companies was 37, with some observations during 2015 – 2019 as many as 185 company years—tests using balanced panel regression using E-Views. The assessment of sustainability disclosure in the annual report uses the 2016 GRI index, which consists of universal (100), economic (GRI 200), environmental (GRI 300) and social (GRI 400) standards. The test results provide empirical evidence that the number of audit committee members has a negative effect on sustainability disclosure. The expert background of the audit committee members in the fields of accounting and finance has a positive effect on sustainability disclosure. The sustainability disclosure will be more qualified if the audit committee members have a financial background. Other independent variables, such as independence and meeting frequency, do not affect sustainability disclosure. This research implies that the amount and background of knowledge or expertise of audit committee members in the financial sector can improve the quality of sustainability disclosure.